The influence of coaches leadership style towards cohesiveness among high school team sports athletes - Embi, Mohd Zainuri; Omar Fauzee, Mohd Sofian; Abdullah, Maria Chong (2011)
The study was conducted to investigate the influence of coach leadership and cohesiveness among high school team sport athletes in the state of Selangor, Malaysia. These studies include the relationship of leadership style and team cohesion and leadership contributions to the integration team athletes. A total of 130 athletes on the team aged between 16 and 19 years. Participants completed all questionnaires Leadership Scale for Sports (LSS), which consists of 40 questions which measure five leadership coach and Scale Integration Group (GEQ), which consists of 18 questions that measure dimensions of cohesion. The findings showed that two leadership coaches who have significant influence on the Democratic style (r = .178, p < .05) and social support (r = .262, p < .01). The results also showed that the influence of coach leadership on the integration task force social support (β=.366, p< .01) and Style Instruction and Training (β =-.212, p<.05) are significant predictors of the team cohesiveness. Some suggestions were also given for future research.